PENGARUH IKLAN NIKE VERSI “JUST DO IT” DI TWITTER TERHADAP KESADARAN MEREK PADA KOMUNITAS FUTSAL GOR PANAM RAYA SQUARE - Hanifan Fauzi; Suyanto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
In this era of globalization, changes occur so quickly in the economic, social, cultural. This naturally brings about changes in the needs and interests of human beings as consumers increasingly complex. Manufacturers have to change and adjust marketing strategies and product patterns according to the situation, conditions and demands of consumers today. This is clearly evident in the marketing concept which was originally only a product-oriented and sales (product concept and sales concept), is now developed with the aim of providing a specific product brand awareness. In achieving this goal Nike brings the concept of advertising through social media twitter to introduce to consumers of products made. In theory S-O-R (Stimulus Organism Response) suggests that social behavior can be understood on an analysis of a given stimulus and can affect the reactions that occur. Users get a stimulus from advertising media witnessed then organize them in mind for later recall the ads they see. The purpose of this study, is to determine whether there is influence between Nike commercial version of "Just Do It" via social media twitter @Nike towards brand awareness in the community futsal Panam Raya Sports Hall Square.The method used in this study is a quantitative method of explanation.. The number of samples for this study were 66 respondents. Sampling using random sampling techniques. To determine how much influence these two variables, the researchers used a simple linear regression analysis. Questionnaire for data processing, carried out using the program Statistics Product And Service Solutions(SPSS) version of Windows 17. Results of research on the effect of advertising nike version of "just do it" on Twitter to brand awareness in the community futsal sports hall panam highway square obtained regression coefficient values in this study is Y = 0.792 + 0.740 X with a significance level of 0.000, which is smaller than α = 0 05. What this means is that there is influence between nike ad version of "just do it" on Twitter to brand awareness in the community of futsal GOR Panam Square, with the effect of 58.4% were categorized as being influential. These percentages show that brand awareness futsal community Panam Sports Hall Square can be met. Thus H0 is rejected and Ha accepted.Keywords : Media Online, Twitter, Brand Awareness, NIKE, Futsal Community